GENDER CHARACTERISTICS OF ADVERSE DRUG REACTIONS DEVELOPMENT: EXPERIENCE OF REGIONAL DATABASE ANALYSIS - A. V. Matveev; A. E. Krasheninnikov; E. A. Egorova; E. I. Konyaeva; N. V. Matveeva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2022)
The aim of the article is the gender characteristics study of the adverse drug reactions (ADRs) development based on the data of the notification forms registered in the regional database ARCADe (Adverse Reactions in Crimea, Autonomic Database), for the period from 2009 to 2018.Materials and methods. The objects of the study were 6903 notification forms about adverse drug reactions recorded in the regional database called ARCADe (Adverse Reactions in Crimea, Autonomic Database) for the period from 2009 to 2018. The classification of drugs for separate pharmacological groups was carried out using the codes of the Anatomical Therapeutic Chemical (ATC) classification system of the World Health Organization (WHO) medicinal products, the instructions data of the State Registers of medicinal preparations used in the Russian Federation and Ukraine (for the cases registered before the entry of the Republic of Crimea into the Russian Federation).Results. A general analysis of the number of cases of the adverse drug reactions (ADRs) development in patients of different genders made it possible to determine that 59.9% (4132 notification forms) of ADRs cases were observed in female patients; 37.7% (2602 cases) - in male patients. In 169 cards (2.4%), information about a patient's gender was missing. The groups with the largest number of the registered cases of ADRs were antimicrobial agents for a systemic use (2864 cases, 41.5% of the total number of the ADRs registered cases), the drugs affecting the cardiovascular (811 cases, 11.7%) and nervous (734 cases, 10.6%) systems. In each of the presented groups, the incidence rate of ADRs in female patients exceeded that in men.Conclusion. The study of the gender characteristics of the pharmacotherapy safety, carried out on the basis of the notification forms of the ADRs data registered in the Republic of Crimea, confirmed a higher likelihood of developing ADRs in female patients. This may be due to the peculiarities of the pharmacokinetics and pharmacodynamics of drugs in the female body, psychological factors, a more frequent use of drugs by this category of people. The implementation of the drug, taking into account specific features of each gender, can lead not only to better treatment outcomes, but also to increased patients' compliance.